Quantum chemical calculation, performance of selective antimicrobial activity using molecular docking analysis, RDG and experimental (FT-IR, FT-Raman) investigation of 4-[{2-[3-(4-chlorophenyl)-5-(4-propan-2-yl) phenyl)-4, 5-dihydro- 1H- pyrazol-1-yl]-4-oxo-1, 3- thiazol-5(4H)-ylidene} methyl] benzonitrile. Issue 7 (July 2021) - Shanmugapriya, N.; Balachandran, V.; Revathi, B.; Narayana, B.; Salian, Vinutha V.; Vanasundari, K.; Sivakumar, C.
Abstract: The research received a great deal of worldwide attention due to the nature of interpretation before the experimental process. Based on the systematic process the structure of thiazole -pyrazole compound 4-[{2-[3-(4-chlorophenyl)-5-(4-propan-2-yl) phenyl)-4, 5-dihydro- 1H- pyrazol-1-yl]-4-oxo-1, 3- thiazol-5(4H)-ylidene} methyl] benzonitrile [CPTBN] was investigated. In the first level, the spectral statistics on experimental FT-IR and FT- Raman was reported. At the next level, geometrical parameters was theoretically acquired from density functional theory (DFT) using B3LPY/6-31G and 6-311G basis set. The computed Wavenumber were collected and compared with the experimental data. The vibrational modes were interpreted in terms of potential energy distribution (PED) results. The FMO, MEP, and NBO analysis further validated the electrophilic and nucleophilic interaction in the molecular systems. Two grams-positive bacteria: staphylococcus aureus, Bacillus subtilis and two gram-negative bacteria: Esherichia coli, Pseudomonas aeruginosa was performed for antibacterial activity. Two fungal strain Candida albicans and Aspergillus Niger was carried out against a ligand using anti-fungal activity. The molecular docking analysis explores the antimicrobial and selective potential inhibitory nature of the binding molecule. Besides, RDG and ELF analysis were also performed to show the nature of interactions between the molecule. Abstract : Thiazole, DFT, RDG, ELF, Docking, Antimicrobial activity